Identifying a wide range of mutations in the BRAF gene for prescribing targeted drugs for melanoma treatment - A. N. Toropovskiy; A. G. Nikitin; A. V. Solov'ev; R. M. Khuzina; O. N. Pavlova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Melanoma is an aggressive malignancy of the skin and mucosa of neuroepithelial nature, heterogeneous both in phenotype and molecular genetic characteristics, with a high risk of progression and a steadily increasing incidence of about 5% a year. The development of melanoma is due to both external (UV exposure) and internal factors, the main ones being mutations in oncogenes and tumour suppressor genes. Hyperactivation of RAS/RAF/MEK/ERK signalling pathway is observed in 75% of skin melanoma cases, and one of its key factors is serine threonine kinase encoded by BRAF gene. Oncogenic mutations of BRAF mimic the phosphorylation of the activation loop of the protein, which results in BRAF being in a permanently activated state. Subsequent operation of the MAPK signalling pathway in a non-stop mode and loss of BRAF negative feedback leads to uncontrolled cell growth and proliferation. The most common mutations in the BRAF gene are p.V600E (valine replacement for glutamic acid), which accounts for up to 95% of all BRAF-mutant melanomas, and p.V600K (valine replacement for lysine), which can account for up to 20% of cases or more. Development of non-selective and selective inhibitors of mutant BRAF protein make mutation in this gene a predictive marker of response and efficacy of targeted therapy.